2020
DOI: 10.1007/s40744-020-00195-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Symptom Severity of Patients Reporting Systemic Lupus Erythematosus in the PatientsLikeMe Online Health Community: A Retrospective Observational Study

Abstract: Introduction: Online health communities and research networks such as PatientsLikeMe (PLM) capture patient perspectives of diseases, including systemic lupus erythematosus (SLE). We performed a retrospective observational study of data provided by patients in the PLM SLE community to characterize demographics, clinical characteristics, patient experience, and symptom impact. Methods: Adults who registered with PLM in 2011-2017 and reported SLE diagnosis and treatment with one or more SLE-related drug (antimala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
(59 reference statements)
1
9
0
Order By: Relevance
“…S2). Given that Nfkbiz ΔK5 mice spontaneously develop Sjögren syndrome-like inflammation, that Sjögren syndrome is observed in about 20% of patients with SLE (22)(23)(24), and that anti-SS-A antibody and anti-SS-B antibody are also detected in patients with SLE (25,26), we examined whether Nfkbiz ΔK5 mice developed the features of SLE. We found that Nfkbiz ΔK5 mice had significantly increased anti-double-stranded DNA (dsDNA) antibodies and anti-Sm antibodies and serum levels of creatine, suggesting that Nfkbiz ΔK5 mice could be used for a mouse model of both Sjögren syndrome and SLE (Fig.…”
Section: Increased S Aureus Skin Colonization Enhances the Developmen...mentioning
confidence: 99%
“…S2). Given that Nfkbiz ΔK5 mice spontaneously develop Sjögren syndrome-like inflammation, that Sjögren syndrome is observed in about 20% of patients with SLE (22)(23)(24), and that anti-SS-A antibody and anti-SS-B antibody are also detected in patients with SLE (25,26), we examined whether Nfkbiz ΔK5 mice developed the features of SLE. We found that Nfkbiz ΔK5 mice had significantly increased anti-double-stranded DNA (dsDNA) antibodies and anti-Sm antibodies and serum levels of creatine, suggesting that Nfkbiz ΔK5 mice could be used for a mouse model of both Sjögren syndrome and SLE (Fig.…”
Section: Increased S Aureus Skin Colonization Enhances the Developmen...mentioning
confidence: 99%
“…14 Many online patient communities exist around the world but are not necessarily dedicated to rheumatology (e.g. PatientsLikeMe, 15 HealthUnLocked, Inspire, Carenity). The information provided individually and voluntarily by patients who are members of these online communities is a new resource for identifying and understanding precisely how health products are used, assessing their effectiveness, quantifying potential adverse effects in real-life situations, detecting subtle signs that are significant for experts in pharmacovigilance and addiction studies, and developing new assessment tools to help form new working hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first published analysis of real-world data gathered on CKD from an online community. Data from PLM have previously been used to explore patient perspectives on neuromyelitis optica and neuromyelitis optica spectrum disorders [ 19 ], characterize the profiles of patients with atopic dermatitis [ 22 ] and systemic lupus erythematosus [ 23 ], and understand patient preferences for type 2 diabetes self-management [ 24 ]. This is the first study to utilize the PLM network to gain insights into self-reported experiences in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%